IMPLICATIONS OF AMAHUSU TOURISM VILLAGE, IN NUSANIWE DISTRICT, AMBON CITY - Latupapua, Yosevita Th; E Siahaya, Troice (LPPM Univ. Ibn Khaldun Bogor, 2023)
Currently, the tourism sector is a push factor in increasing regional income in Maluku, especially Ambon city besides fisheries. The natural and cultural potential possessed by Ambon City as a Maritime City and Local Culture, provides a special charm for the city government in developing existing potential as part of a tourism development destination. The community's role in realizing the development of a tourist village in Amahusu is not yet optimal, so this PKM is carried out to provide socialization to the community in increasing understanding and more optimal preparation in supporting the development of the Amahusu tourist village. The method applied to the community is socialization, pre-test, and post-test. The results obtained show an enthusiastic attitude from the participants in participating in socialization activities. This attitude shows a good response from the community to obtain additional knowledge, and capture interest. Collaboration with academics in supporting the development of more optimal tourist villages to attract tourist visits